2020
DOI: 10.3389/fcvm.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Comparing WatchmanTM and Amplatzer Devices for Stroke Prevention in Atrial Fibrillation

Abstract: Background: For patients with atrial fibrillation who are at high risk for bleeding or who cannot tolerate oral anticoagulation, left atrial appendage (LAA) closure represents an alternative therapy for reducing risk for thromboembolic events.Objectives: To compare the efficacy and safety of the Amplatzer and Watchman TM LAA closure devices.Methods: A meta-analysis was performed of studies comparing the safety and efficacy outcomes of the two devices. The Newcastle-Ottawa Scale was used to appraise study quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
2
10
1
1
Order By: Relevance
“…Such a high incidence of the leak in the WD group was due to cutoff value > 3 mm for the severe residual leak. These data correlated well with the results of the aforementioned meta-analysis [ 15 ]. The rate of total peridevice leakage was significantly higher in the WD group (log OR = 1.32; 95%CI = 0.76 to 1.87; p < 0.01).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Such a high incidence of the leak in the WD group was due to cutoff value > 3 mm for the severe residual leak. These data correlated well with the results of the aforementioned meta-analysis [ 15 ]. The rate of total peridevice leakage was significantly higher in the WD group (log OR = 1.32; 95%CI = 0.76 to 1.87; p < 0.01).…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of two European real-world registry data, performed by Kleinecke et al [ 14 ] reported a comparable periprocedural major complications rate for the WD and Amplatzer group devices (4.1% vs. 6.0%, p = 0.32). A recent meta-analysis of six studies also confirmed the comparable safety outcomes for the WD and Amplatzer groups [ 15 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The Watchman is the only FDA approved LAA closure device with PROTECT [21] and PREVAIL [22] randomized clinical trials demonstrating non-inferiority to oral anticoagulant (warfarin) for ischemic stroke protection but not overall efficacy. Recently, a meta-analysis comparing Watchman and Amplatzer devices for stroke protection resulted in similar low complication and event rates findings with comparable efficacy and safety results [23]. There are also many other emerging LAA mechanical device technologies in various stages of pre-clinical development [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Близкие результаты были получены и в других обсервационных и регистровых исследованиях. Так, результаты 6 небольших наблюдательных исследований, сравнивающих ACP/Amulet и Watchman, были обобщены в мета-анализе I. Basu Ray [15] и соавторов. Всего были суммированы данные по 614 пациентам.…”
Section: рис 3 частота достижения суммарной клинической эффективности в группах сравненияunclassified